Conceptual View of the Implementation of the Nuclear Energy Program in the Republic of Kazakhstan - Erlan Batyrbekov; Vladimir Vityuk; Denis Zarva; Mazhit Sharipov (Energies)
This paper presents an analysis of the existing prerequisites and opportunities for the start-up of the Republic of Kazakhstan’s own full-fledged Nuclear Energy Program, a conceptual vision of the development of the Kazakhstani nuclear industry. Recommendations have been formulated for the timely and successful implementation of the program for the introduction of nuclear power plants into the country’s energy generation structure, the development of the necessary related nuclear infrastructure facilities, national legislation, and other issues directly related to nuclear power development.